Exploring ecosophical tenets of posthumanism through O.V Vijayan’s The Infinity of Grace - Pavithran, Haritha; Sivakami, B. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The paper attempts to unravel newer ecosophical dimensions of posthumanism through the textual analysis of Ottupulackal Velukkuty Vijayan’s The Infinity of Grace (1987/1999). Posthumanism, a dynamic field of inquiry generally explored in the current context of “bio-, nano-, neuro- and info- technologies” also refers to what Rosi Braidotti calls an “enlarged sense of interconnectedness between self and the other.” Braidotti, while reinventing the posthuman subjectivity, bases it on an ecosophy that merges technological, geological, and biological dimensions. In this context, the paper argues how the spiritually rooted Indian environmental philosophy offers new perspectives to look at Braidotti’s relational model of ecosophy through the analysis of the chosen text. Using Braidotti’s theoretical concepts, zoe-centrism, symbiotic becoming, and nomadic subjectivity, this paper presents insights into the formation of individual subjectivity through the characters’ interaction with their physical and mental environments and its rootedness in Indian environmental philosophy. In doing so, the study reveals a guru-shishya trope, a trope that generally depicts a mentor-disciple relationship among the nonhuman and human entities. By focusing on this trope, the role of Vijayan’s writings in contributing to the expanding eco-philosophy of posthumanism may be foregrounded.